De inconstantes e preguiçosos a trabalhadores exemplares : o discurso administrativo sobre as populações indígenas nos pueblos de indios do Rio da Prata (1768-1800) - Lema, Fabrício Ferreira de (2022)
The expulsion of the Jesuits from the American territories, carried out in 1768, was marked by intense changes in the political management of spaces that ware almost 150 years under their exclusive aegis. The representatives of the Crown, delegated to fulfill the royal designs, were responsible for elaborating and implementing a series of reform proposals whose fundamental aim was to bring the inhabitants of the missions to a fully “civilized” life. Along with this effort, it was necessary for Crown agents to make indigenous behaviors thinkable in their narrative - as it was essential to understand their skills and abilities to access the ideas of “progress” projected by the authorities. The purpose of this investigation, therefore, was to understand how this process took place, the result of which was the elaboration of a particular image of the indigenous populations that occupied these territories. Analyzing the reports, memorials, summaries, and other productions written by the colonial authorities, we seek to understand how the construction of the figure of the indigenous people changed due to the needs of the new administration, as well as the procedures used by the narrators. The time frame was established according to this change that was noticed in the administrative discourse, since the elaboration and implementation of Francisco de Bucarelli's Ordenanzas, in 1768, until the formal “release” of some indigenous families by Viceroy Gabriel de Avilés, in 1800. During this period, the native inhabitants turn from “fickle and lazy to exemplary workers”. From François Hartog's propositions, we retrieved those predicates associated to the “Indian” figure inside such discourse. In line with Roy Wagner's Theory of Contexts, we argue that different “associations” to the indigenous condition shaped what we call a particular form of “rhetoric of enlightened Otherness”. This procedure was supported by Michel de Certeau's affirmation that such texts show an eminent literary dimension on which is possible to question how “discourses on the Other” are built.